Long term use of hydraulic artificial urethral sphincters in nine dogs from New Zealand with urethral sphincter mechanism incompetence. Issue 4 (4th July 2018) - Morgan, KRS; Milner, HR; Tikekar, A; Smith, HL; Coomer, AR
Abstract: AIMS: To report on the long-term outcomes of hydraulic artificial urethral sphincter (HAUS) placement for the correction of urethral sphincter mechanism incompetence (USMI) in New Zealand dogs. METHODS: Retrospective data were obtained from cases of dogs which had a HAUS placed after failed medical and/or surgical management of USMI between August 2012 and November 2016. Owner assessment of urinary incontinence was evaluated by an online survey in May 2017 using a visual analogue scale (0 being normal, 100 being severely affected) for the frequency, volume and severity of any straining to urinate, immediately prior to the placement of the HAUS and at the time of the survey. The number of days between surgery and the completion of survey were recorded. RESULTS: Seven females and two male dogs, which were all desexed except for one female, were eligible for inclusion in the study. The period of follow-up following HAUS placement ranged from 206–1, 685 days. Following HAUS placement, frequency and volume of urinary incontinence decreased for six dogs and were practically unchanged for three dogs. The median frequency score decreased from 70 to 13 and the volume score decreased from 73 to 12. There was no consistent change in the perceived degree of straining to urinate. Complications occurred in three dogs; one required repositioning of a dislodged injection port, one required management for haematuria and a hypoplastic bladder, and one required surgical removal of fibrous tissue around the HAUS cuff. CONCLUSIONS AND CLINICAL RELEVENCE: HAUS placement was an effective method for the treatment of persistent USMI in most dogs and provided good clinical results based on owner assessment. The technique was associated with few complications and allowed successful long-term control of urinary incontinence without the need for medical management.